Anxious Robots, Desiring Repression, Generating Profit - Chau, Christina; Savat, D. (Central Queensland University, 2017)
Robots are increasingly playing roles in everyday life. These roles range from doing the vacuuming, to assisting in surgery, to stocking shelves, to assisting teaching children with autism, to providing care and entertainment for the elderly. This essay deals less with robots themselves, however, and more with the particular anxieties that surround the use of robots. Critical to our argument is that robots are not separable from human being, just as humans are inseparable from machines. They are better thought of as fragments of human subjectivity that in and of themselves are neither beneficial nor hazardous. Instead we argue, partly through an exploration of the work of Stelarc, that the anxieties around the use of robots reflect an anxiety about the possibility of people’s own machinic nature. The important question to ask, we argue, is how our machines, including robots, affect our own capacity to act, as well as our capacity to be affected. What is at issue is precisely the machines in our own heads, and in particular the production of forms of subjectivity in which we can recognise, or rather fail to recognise, our own becoming robotic, all in the name of capitalism and profit.